Vocal Cord Paralysis after Tracheal Intubation: An Overview of the Etiology and Associated Risk Factors - Anwar, Meerab; Hussain, Komal Ashiq; Anwar, Pervez (International Archives of Otorhinolaryngology, 2025)
Vocal cord paralysis (VCP) is a deprivation of motility and the dysfunction of the vocal cords due to a defect in the vagal nerve or recurrent laryngeal nerve (RLN). It also occurs due to mutilation in the cricoarytenoid joint or posterior commissure scarring after prolonged tracheal intubation. It is a disorder with an extensive range of etiologies reliant on its laterality pattern.To discuss the laterality pattern of VCP due to endotracheal intubation and its respective treatments, the associated etiologies, and the risk factors, to provide a new direction to physicians for its treatment and to avoid its occurrence.We conducted a peer review of many of the articles published to date on VCP. An analysis of 967 patients from 5 studies determined that unilateral VCP (UVCP) is three times more frequent than bilateral VCP (BVCP). Furthermore, we analyzed 2,232 patients from 6 different studies that concluded surgery was the most common cause, followed by neoplastic diseases or malignancies. Another important though highly uncommon etiology of VCP is endotracheal intubation; however, it is disturbing for doctors as endotracheal intubation is a common procedure for general anesthesia.A variety of factors may cause VCP, including age, comorbidities, body mass index BMI, the duration of the intubation, the handling of the apparatus, operative time, and tracheal tube sizes. Preventive measures should be prioritized to avoid severe consequences, and intubation must be performed carefully in elderly people and in subjects with lower BMIs. Knowledge of the risk factors will help physicians customize intubation procedures in the future.
Keywords: vocal cord; etiology; idiopathic; intubation; comorbidities